In the Kaleidoscope of Utopia. Stanisław Czycz’s Expedition to the Boundaries of Literature - Pachocki, Dariusz ((Dif)fusions: Relations between Literature and Art in Poland after 1945, 2019)
The article concerns the utopian project of Stanisław Czycz entitled Arw. Andrzej Wajda, who ordered Czycz’s script (or stories that could be its basis) for the film devoted to the life and work of prematurely deceased painter Andrzej Wróblewski, contributed to the creation of this text. The writer approached the task in a non-standard way, creating a text, which he left in the manuscript (or rather a score) entitled Arw. His work, both in its structure and the semantic layer, does not respect traditional reading habits, i.e. linear reading. The article focuses both on the interactive presentation technique used by Czycz, as well as on references to paintings contained in the text.